Development of KISS1 knockout pigs is characterized by hypogonadotropic hypogonadism, normal growth, and reduced skatole† - Ahern, Daniel F.; Martins, Kyra; Flórez, Julio M. [UNESP]; Ross, Caitlin E.; Huisman, Abe; Cushman, Robert A.; Shuping, Sydney L.; Nestor, Casey C.; Desaulniers, Amy T.; White, Brett R.; Sonstegard, Tad S.; Lents, Clay A. (Oxford University Press (OUP), 2024)
Kisspeptin is a major regulator of gonadotropin secretion in pigs. Previously, CRISPR/Cas9 knockout of KISS1 was used to develop a mosaic parental line of pigs to generate offspring that would not need castration due to loss of kisspeptin. The current goal was to characterize growth and reproductive development of F1 pigs from this parental line. Body weights, gonadotropin concentrations and gonadal development were measured from birth through development (boars to 220 days of age, n = 42; gilts to 160 days of age, n = 36). Testosterone, skatole, and androstenone were also measured in boars. Blood samples were collected by jugular venipuncture for quantification of serum hormones, gonadal tissues were collected for gross morphology and histology, and a fat biopsy was collected (boars) for skatole and androstenone analysis. Body weight did not differ with genotype. There were no differences between KISS1+/+ and heterozygote KISS1+/- animals for most parameters measured. Gonadotropin concentrations were reduced in KISS1-/- boars and gilts compared with KISS1+/+ and KISS1+/- animals (P < 0.05). Concentrations of testosterone in serum and both androstenone and skatole in adipose were less in KISS1-/- boars than in KISS1+/+ and KISS1+/- boars (P < 0.05). Hypogonadism was present in all KISS1-/- gilts and boars. These data indicate that knocking out KISS1 causes hypogonadotropic hypogonadism but does not negatively affect growth in pigs. Only one KISS1 allele is needed for normal gonadotropin secretion and gonadal development, and accumulation of compounds in adipose leading to boar taint.
Keywords: development; follicle-stimulating hormone; kisspeptin; knockout; luteinizing hormone; reproduction; skatole; swine; testosterone